Strategi Pembentukan Jiwa Kewirausahaan Santri Melalui Program Kopontren (studi Kasus di Pondok Pesantren Darussaadah Gubugklakah Poncokusumo Malang ) - Dhiaul Haq; Akhmad Said (STAI Ma'had Aly Al-Hikam Malang, 2019)
Kopontren is an economic institution that is located in a boarding school environment, and is a medium for students to carry out work practices so that there is a balance of patterns of religious education and entrepreneurship education. The existence of kopontren is one of thhe meanss of education foor students to foster interest and entrepreneurial talent with entrepreneurship education. that is hopeed that students will be able to eqeuip students with various abilitiees and skills, especially with regard to the needs of the community and in the field of employment. What program strategies are applied at thekopontren in shaping the entrepreneurial spirit of students at Darussaadah Gubugklakah poncokusumo Malang Islamic boarrding school, (3) what are the factors that hinder the program of the kopontren in shaping the entrepreneurial spirit of students of Darussaadah gubugkalakh poncokusumo Malang, (3) what are the solutions conducted to overcome the failure applied by the Kopontren in shaping the entrepreneurial spirit of the students of Darussaadah Gubugklakah Poncokusumo MalangTo achieve the above objectives, qualitative research approaches are used. the focus of the research is the santrii Entrepreneurship Soul Formation Strategy through the Darussaadah Islamic Boarding School Kopontren program poncokusumo Malang, the data collection was carried out by interview, observation, and documentation. Data analysis was performed by data reduction and finally the data compiled was drawn to a conclusion. Triaungualition of the validity of the data is checked, and comparing research data with interviews and documents.The result of this study indicate that : (1) the Strategies used in shaping the entrepreneurial spirit of the s using training and fostering education about entrepreneurship, are carried out on Friday, and every time there is education and training that is held at the Darussaadahh Vocational School. One of the educational training processes is to foster honesty, creative, and innovative values, and in accordance with entrepreneurial characteristics. Mental development is very important that is needed for entrepreneurial independence. (2) the inhibiting factors faced by the Kopontren namely, students lack honesty, lack self-confidence, do not understand quality goods, (3) and solutions to overcome the inhibiting factors namely the Kopontren management must be vigilant and more stringent in maintaining the Kopontren, provide direction and guidance on an incentive basis, so that they can be serious in carrying out guidance and coaching to form an entrepreneurial spirit.